Kombinasi Kompres Kubis Dingin & Pembebatan Payudara Untuk Mengurangi Ketidaknyamanan & Pembengkakan Payudara Pada Ibu Dengan Intrauterine Fetal Death - Annisa Hilalriah; Riski Oktavia; Eny Hernani (Universitas Muhamadiyah Manado, 2023)
Engorgement of the breast are a condition that is prone to occur for mothers with IUFD. This is because the milk is not completely emptied, but left alone, causing the milk to remain inside and the breasts to swell. Nursing Intervention Combination of Cold Cabbage Compresses and Breast Bandaging is an effort to reduce breast discomfort and swelling in women with IUFD. The research method uses case studies with pre-post intervention. The sample of this study was 1 post IUFD mother on the first day. The measuring instrument used the Numeric Rating Scale (NRS) to measure pain scale and the Six Point Engorgement Scale (SPES) Check List to measure the scale of breast swelling experienced in post partum mothers with IUFD. The combination intervention of Cold Cabbage Compresses and Breast Bandaging was carried out for 3 days when the patient was hospitalized 2-3 times/day and observations were made to find out complaints of pain and swelling in the mother's breasts. The results showed a decrease in the level of pain scale (from scale 4 (moderate) to scale 0 (no pain) and breast swelling scale (from scale 5 to scale 1 (breasts felt soft)) in respondents after 3 days of intervention. Conclusions Combination Compresses Cold Cabbage and Breast Bandaging are effective for reducing breast discomfort and swelling in women with IUFD.